High School English Grammar and Composition - Wren & Martin; Wren & Martin (Karachi, Pakistan Paramount Publishing Enterprise, 1973)
This book provides essential grammar rules and composition skills for high school learners. It covers parts of speech, sentence structures, syntax, writing techniques, and practical exercises to improve English language proficiency.
A classic and comprehensive grammar guide for high school students; includes explanations, examples, and composition exercises.
Keywords: High School English Grammar and Composition